Ex-vivo Sensitivity of Plasmodium falciparum to Common Anti-malarial Drugs: The Case of Kéniéroba, a Malaria Endemic Village in Mali - Karim Traoré; Seidina A. S. Diakité; Sekou Bah; Drissa S. Konaté; Djeneba Dabitao; Ibrahim Sanogo; Modibo Sangaré; Souleymane Dama; Bourama Keita; Mory Doumbouya; Merepen A. Guindo; Seydou Doumbia; et al. (Drugs in R&D, 2020)
Abstract Background In 2006, the National Malaria Control Program in Mali recommended artemisinin-based combination therapy as the first-line treatment for uncomplicated malaria. Since the introduction of artemisinin-based combination therapy, few reports are available on the level of resistance of Plasmodium falciparum to the most common anti-malarial drugs in Mali. Methods From 2016 to 2017, we assessed the ex-vivo drug sensitivity of P. falciparum isolates in Kéniéroba, a village located in a rural area of southern Mali. We collected P. falciparum isolates from malaria-infected children living in Kéniéroba. The isolates were tested for ex-vivo sensitivity to commonly used anti-malarial drugs, namely chloroquine, quinine, amodiaquine, mefloquine, lumefantrine, dihydroartermisinin, and piperaquine. We used the 50% inhibitory concentration determination method, which is based on the incorporation of SYBR® Green into the parasite’s genetic material. Results Plasmodium falciparum isolates were found to have a reduced ex-vivo sensitivity to quinine (25.7%), chloroquine (12.2%), amodiaquine (2.7%), and mefloquine (1.3%). In contrast, the isolates were 100% sensitive to lumefantrine, dihydroartermisinin, and piperaquine. A statistically significant correlation was found between 50% inhibitory concentration values of quinine and amodiaquine (r = 0.80; p < 0.0001). Conclusions Plasmodium falciparum isolates were highly sensitive to dihydroartermisinin, lumefantrine, and piperaquine and less sensitive to amodiaquine (n = 2), mefloquine (n = 1), and quinine (n = 19). Therefore, our data support the previously reported increasing trend in chloroquine sensitivity in Mali.